2020
DOI: 10.1063/1.5127936
|View full text |Cite
|
Sign up to set email alerts
|

Photon waiting-time distributions: A keyhole into dissipative quantum chaos

Abstract: Quantum systems, when interacting with their environments, can exhibit complex non-equilibrium states that are tempting to be interpreted as quantum versions of chaotic attractors. Here we propose an approach to open cavity dynamics based on the unraveling of the corresponding master equation into an ensemble of quantum trajectories. By using the concept of "quantum Lyapunov exponents" [I. I. Yusipov et al., arxiv: 1806.09295], we demonstrate that 'chaotic' and 'regular' regimes of the intra-cavity dynamics ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 55 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…In our prior work 17 , we found that the transitions to chaotic photonic regimes in an open Kerr-nonlinear cavity are associated with appearance of power-law intermediate asymptotics, PDF(∆t) ∼ ∆t −α , in the corresponding waiting time pdf (which otherwise decays exponentially) 17 . We expect that this effect is generic and will emerge also in the considered spin-photonic model.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In our prior work 17 , we found that the transitions to chaotic photonic regimes in an open Kerr-nonlinear cavity are associated with appearance of power-law intermediate asymptotics, PDF(∆t) ∼ ∆t −α , in the corresponding waiting time pdf (which otherwise decays exponentially) 17 . We expect that this effect is generic and will emerge also in the considered spin-photonic model.…”
Section: Resultsmentioning
confidence: 96%
“…The dynamics of the photonic mode in the periodically modulated in time Kerr-nonlinear cavity 17 serves us a reference case and a background to project our results on. Equations (1)-(4) reproduce this case when we set δ = 0, g = 0, ω = 0.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations